Isolated Single Umbilical Artery as a Risk Factor for Urinary Tract Infections in Childhood - Willner, Nata Tifferet; Wainstock, Tamar; Walfisch, Asnat; Sheiner, Eyal; Landau, Daniella; Beharier, Ofer (American Journal of Perinatology, 2019)
Objective This study aimed to determine whether isolated single umbilical artery (iSUA), even absent identifiable genitourinary (GU) abnormalities, increases the risk of GU infection during childhood.Study Design Retrospective population-based comparison of fetuses with iSUA versus normal three-vessel cords. Fetuses with growth restriction, prematurity, multiple gestations, and anatomical or chromosomal anomalies were excluded. The primary outcome was hospital-associated GU infection during the first 18 years of life. Kaplan–Meier's survival curves were used to assess cumulative risk; Cox's multivariable models were used to adjust for confounders.Results Among 227,599 term singleton deliveries, children with iSUA (n = 729) had a higher incidence (1.8 vs. 0.6%, p < 0.001) and cumulative incidence (log-rank test, p < 0.001) of hospital-associated GU infection. The Cox's models confirmed these findings (hazard ratio: >2.82, confidence interval: 1.63–4.87 in composite models).Conclusion iSUA represents an independent risk factor for GU infection. Urinary tract imaging may be warranted.
Keywords: single umbilical artery; genitourinary infection; urinary tract infection; umbilical vessel; fetus